Análise ergonômica da interface conjunto aluno individual de uma instituição pública municipal de ensino - Vaqueiro, Ana Júlia [UNESP]; Ercolini, Sofia Tafuri [UNESP]; Aranda, Lívia Sardella [UNESP]; Simões, Danilo [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The application of ergonomics aims to ensure greater efficiency in activities and learning, is essential in the educational process. It provides physical and psychological comfort when adapted to the anthropometric measurements of the students. Thus, the study aimed to examine the student school furniture interface, considering the anthropometric profile of students of a public school. The anthropometric profile have been obtained through height measurements of the students bodys in a standing position by means of a measuring tape attached vertically to the ground. To verify the adequacy ergonomic of school furniture, measurements were made of chairs and tables for individual student set also with a measuring tape help. From the analysis, it was concluded that the height of the middle point (point S), the depth of top and its height, did not correspond with the Regulatory Brazilian Norm. However, 70% of school furniture was in compliance with the Norm.

A ergonomia, quando aplicada ao processo educacional, visa proporcionar conforto físico e psicológico aos estudantes e, consequentemente pode assegurar um maior rendimento das atividades e do aprendizado. Destarte, o estudo teve como propósito analisar a interface alunomobiliário escolar, ponderando o perfil antropométrico dos estudantes de uma escola pública municipal. O perfil antropométrico foi obtido a partir da medida direta do corpo dos estudantes na posição em pé, por meio de uma trena métrica fixada verticalmente ao solo. Para a verificação da adequação ergonômica do mobiliário escolar, foram realizadas mensurações das cadeiras e mesas para conjunto aluno individual também com auxílio de uma trena métrica. A análise dos dados permite concluir que a altura do ponto médio do encosto (ponto S), a profundidade do tampo, bem como sua altura, não estão em conformidade à Norma Brasileira Regulamentadora empregada no estudo. Contudo, 70% das características do mobiliário escolar estão em consonância à referida Norma.
Keywords: Comfort; Anthropometry; Human engineering; Conforto; Antropometria; Engenharia humana